Differential technology development: speeding up to slow down disasters? - Sandberg, A (Coimbra University Press, 2024)
One of the earliest attempts at steering and applying technology in a socially beneficial way may have been Mohism, the school of Mo Zi during the Warring States era in China. Being committed to a harmonious (if authoritarian) peaceful social order they tried to dissuade rulers from attacking other states – and to develop and spread knowledge of defensive warfare, aiding cities and states under attack2. The aim was to make aggressive war impractical. This may also be the earliest attempt to speed up certain technologies to reduce the harm done by other technologies.